Perfil epidemiológico de pacientes del servicio de hospitalización domiciliaria de una institución de nivel tres en el Valle de Aburrá, 2015 (2019)
ABSTRACT: To describe the epidemiological profile of patients referred to the home hospitalization service by a level 3 institution in the Aburrá Valley, in 2015. Methodology: Cross-sectional descriptive study of treated patients (n = 4956 patients and 109 032 records). The source of information corresponds to the 2015 database of the home care service of a level 3 institution in the Aburrá Valley. Distribution was determined by age, sex, type of pathology, spatial location and type of treatment management. Results: The service was provided mostly to women (55%) with ages between 50 and 90 years. Patients came mainly from socioeconomic strata 1, 2 and 3, belonging to the contributory regime. The four main pathologies are: skin and subcutaneous tissue diseases (CIE-10 L00-L99, 32%) associated with management of surgical wounds, genitourinary system diseases (CIE-10 N00-N99, 21%), respiratory diseases (CIE-10 J00-J99, 18%) and infectious and parasitic diseases (CIE-10 A00-B99, 7%). Conclusions: Home hospitalization in the Aburrá Valley focuses in the care of the elderly, especially women over 50, whose management plan involves the supply of antibiotics in the majority of cases. Keywords: health profile, prevalence, outpatient care, Colombia.